Factor influences children in family travel decision in East Coast, Malaysia - Wong Sze Yann; Siti Hajar Ahmad; Mohd Asyraf bin Mohd Noor; Siti Aisyah Muhamad Yusuff (2016)
Past studies have shown the influence children have on general product purchase decisions but little is known about children influence on family travel decision. This research sets out to determine the influential factors children have regarding family travel decision to better identify children's role as influencers in the family. Whilst children are not the end decision makers regarding family travel purchases, they should be given recognition about the role they play during the entire process. This research will benefit sectors such as people in the tourism industry and families as well as future researchers. Questionnaires were used to collect data about children influences such as their age, income of parents and product category in family travel decision. The results of the research show children influences have positive relationships with family travel decision. In conclusion, children definitely influence family travel decision, and thus it is crucial to acknowledge children's role in family. Some recommendations for future research will also be presented.